PROSES PENYIDIKAN TERHADAP TINDAK PIDANA ANAK DIKEPOLISIAN SEKTOR JATEN KEPOLISIAN RESOR KARANGANYAR - SULISTYONO SULISTYONO (RECHTSTAAT, 2014)
The objective of research was to find out the investigation mechanism of crime committed by child; in addition adequate data was available to support this research.The data was collected using sociological approach with descriptive analysis specification. To analyze the data, the author employed a normative qualitative method.Considering the result of research and data analysis, it could be concluded that the mechanism of investigating the crime committed by child included: investigating, acting including convening, arresting, detaining, frisking, seizing, and examining including examining the witness/victim, expert and the suspect as well as case document submission. Some constraints the investigators encountered in the field included status quo factor in the venue and infrastructure factor. The strategy of dealing with the constraints in the process of investigating a crime committed by a child was status quo factor in the venue. The measures taken to cope with the constraints emerging was status quo factor in the venue, the closest personnel came to and secured immediately, by means of closing the venue using police line and guarding it. When they arrived at the venue and many people had swarmed over it, they warned the people to keep away from the venue and secured it. Keywords: Investigation, Child Crime, Police